1988
DOI: 10.1128/jb.170.3.1162-1167.1988
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation and structure of the Bacillus subtilis sporulation locus spoIIIC

Abstract: . 146: [430][431][432] 1981) by using as an assay transformation of the mutant allele spoIIIC94 to the wild type. Regulation of the spolliC locus was studied by hybridization of cloned spolliC DNA to RNA pulse-labeled at various times during growth and sporulation. The relative rate of transcription of the spolIlC locus was highest 3 h after the end of growth. The DNA sequence of the spoIlIC transcription unit indicated the coding capacity for a small protein (138 amino acids) having significant similarity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The complete sequence of each protein was derived from the same sources as those in the legend to Fig. 10, except for Sin (14) and SpollIC (11). data banks, no closely related homologs of SenS were found in other organisms.…”
Section: Methodsmentioning
confidence: 99%
“…The complete sequence of each protein was derived from the same sources as those in the legend to Fig. 10, except for Sin (14) and SpollIC (11). data banks, no closely related homologs of SenS were found in other organisms.…”
Section: Methodsmentioning
confidence: 99%
“…However, the gene encoding K was unknown. Genetic studies focused on the spoIIIC locus, which appeared to encode a small protein with high similarity to the C-terminal region of bacterial factors but lacking any corresponding N-terminal region (64). Interestingly, a different gene, spoIVCB, was found to encode a protein similar to the N-terminal region of a factor.…”
Section: Developmental Chromosome Rearrangementmentioning
confidence: 99%
“…Recently, Stragier et al (23) showed that spoIVC cisB and spoIIIC (4) are fused at T3 as a result of DNA rearrangement and that the fused gene encodes the late-sporulation-specific sigma factor K (CrK) (15).…”
mentioning
confidence: 99%